التكييف الفقهي والإشكال التسويقي لنظام الاشتراك الزمني - Abdullah Shaif Tarbosh
This study intends, within its theoretical framework, to arrive at a fiqh characterization of timesharing, a practice bout which the international fiqh academies have not yet delivered a conclusive decision. The means for doing to is to clarify which contractual formats are lawful and which are prohibited. On the practical side, the study aims to examine the actual social problems associated with the contracts of this marketing system and the real reasons behind the slippery practices of its marketers. It also suggests the best solutions and methods for dealing with these problems. The researcher has employed an inductive methodology by examining the concepts and rules related to the fiqh characterization of the contracts of this system. Then an analytic methodology is employed by means of special investigation designed for that purpose in the field study The researcher reached a number of conclusions; among the most important: It is lawful to accept additions and modifications to a timesharing contract; i.e., to precede it with a housing and residence contract that is harmonious with these contracts, which are themselves part of the housing sector and are fundamentally intended for the purpose of housing and which are in reality repetitive leasing contracts. The previous contractual basis of these contracts was sale followed by lease, and as such, they did not accept additions or modifications such as installment payments or the exchange of some units for another before their delivery. The subject of these contracts is housing, which is why the contract currently being applied to them is a contract of construction and development, a composite of istisna' (manufacturing) and ijarah (lease), which does accept additions and modifications due to its compatibility with housing and residence contracts. What should not occur is for these contracts to turn into quasi-salam (forward) contracts that involve delayed delivery of both payment and the counter-value, which would mean sale of a debt for a debt, which is prohibited in the Shari'ah. The parameters of these contracts must be established and observed; that will resolve the legal and organizational problems, as well as the problems associated with their fiqh characterizations The researcher was able to study these contracts as they are actually being applied, and he found that responsibility for the problems associated with them is distributed among three parties: the companies, the customers, and the government. The companies must bear a large share of the burden of responsibility, for they have given salespeople free rein to market them in dubious ways, tainted by fraud, enticement and trickery. Customers also share a portion of the blame for failing to consult those, such as lawyers, who are familiar with the nature of these contracts. They expose their wealth to great risks by failing to fully check out the permits of these companies, to find out how recently they were issued, and whether the contracts have been properly endorsed by the relevant authorities. The government also bears significant responsibility for not being vigilant in deterring those who casually play with the wealth and interests of citizens. Such persons should be arrested, dried, brought to account and subjected to the legal penalties that apply to them. That would, first of all, protect people's rights; moreover, it would contribute to security and stability. Finally, the researcher believes that financial institutions which do not take the trouble to properly define the fiqh characterizations of their contracts have no credibility. Also, there can be no progress without academic field research That correct mistakes and puts industry practice on a paper footing.